Factors Related to Gastritis in Kendari City - Ahmad, Ahmad; Sunarsih, Sunarsih; Amraeni, Yunita (Waluya The International Science of Health Journal, 2023)
Introduction: Based on an initial survey conducted at 15 Public Health in Kendari City, it was found that gastritis increased by 11798 (29.4%). Kendari City population data as many as 401,719 people spread over 15 sub-districts, seen from the annual report of the Kendari City Office. Thus, researchers feel the need to conduct research on factors related to the incidence of gastritis in Kendari City. Methods: This type of quantitative research with a cross sectional design has a population of all patients who come for treatment at 15 Kendari City Health Centers totaling 11798 and a sample of 385 patients. Result: The results of the study stated that of the 385 respondents who declared gastritis there were 201 (52.2%) and 185 (47.8%) respondents stated that they did not have gastritis. Based on statistical tests, it showed that there was a significant relationship between stress and gastritis (p value = 0.000) and smoking on the incidence of gastritis (p value = 0.024) while the variable of diet (p value = 0.000) which means that there is a relationship between diet and the incidence of gastritis in the city of Kendari Conclusion: There is a relationship between stress and gastritis, there is no relationship between smoking and gastritis, and there is a relationship between diet and gastritis.